Theological hermeneutics in the classical Pentecostal tradition : a typological account - Oliverio, L. William, Jr (Global Pentecostal and Charismatic studies, 2012)
In Theological Hermeneutics in the Classical Pentecostal Tradition, L. William Oliverio Jr. accounts for the development of Classical Pentecostal theological hermeneutics through four hermeneutical types and concludes with a philosophical basis for future Pentecostal theological hermeneutics within the contours of a hermeneutical realism.